A microdosing framework for absolute bioavailability assessment of poorly soluble drugs: A case study on cold‐labeled venetoclax, from chemistry to the clinic - Amr Alaarg; Rajeev Menon; David Rizzo; Yemin Liu; Jeffrey Bien; Tricia Elkinton; Timothy Grieme; Lutz R. Asmus; Ahmed Hamed Salem (Wiley, 2022)
Abstract This work presents an end‐to‐end approach for assessing the absolute bioavailability of highly hydrophobic, poorly water‐soluble compounds that exhibit high nonspecific binding using venetoclax as a model drug. The approach utilizes a stable labeled i.v. microdose and requires fewer resources compared with traditional approaches that use radioactive 14C‐labeled compounds. The stable labeled venetoclax and internal standard were synthesized, then an i.v. formulation was developed. In the clinical study, female subjects received a single oral dose of venetoclax 100 mg followed by a 100‐µg i.v. dose of cold‐labeled 13C‐venetoclax at the oral time of maximum concentration (Tmax). The i.v. microdose was prepared as an extemporaneous, sterile compounded solution on the dosing day by pharmacists at the clinical site. Several measures were taken to ensure the sterility and safety of the i.v. preparation. A sensitive liquid chromatography‐tandem mass spectrometry method was developed to allow the detection of plasma levels from the i.v. microdose. Plasma samples were collected through 72 h, and pharmacokinetic parameters were estimated using noncompartmental methods. Postdosing sample analysis demonstrated the consistency of the preparations and allowed the precise calculation of the pharmacokinetic parameters based on the actual injected dose. The absolute bioavailability of venetoclax was estimated at 5.4% under fasting conditions. Venetoclax extraction ratio was estimated to be 0.06 suggesting that the fraction transferred from the enterocytes into the liver is limiting venetoclax bioavailability. The proposed framework can be applied to other highly hydrophobic, poorly water‐soluble compounds that exhibit high nonspecific binding to support the understanding of their absorption and disposition mechanisms and guide formulation development.